2015
DOI: 10.1007/s12192-014-0556-x
|View full text |Cite
|
Sign up to set email alerts
|

ASF1 and the SWI/SNF complex interact functionally during nucleosome displacement, while FACT is required for nucleosome reassembly at yeast heat shock gene promoters during sustained stress

Abstract: Histone chaperones are an integral part of the transcription regulatory machinery. We investigated the involvement of histone chaperones and their functional interactions with ATP-dependent chromatin remodeling complexes in the regulation of yeast heat shock genes. Strong functional interaction between the histone chaperone ASF1 and the ATP-dependent chromatin remodeling complex SWI/SNF is exhibited in synergistic diminishment of nucleosome displacement during heat shock in the ΔASF1/ΔSNF2 strain in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Mutations in SPT16 made the promoter of SER3 accessible for transcriptional factors and therefore derepressed the SER3 gene [78]. Multiple subsequent studies have reported loss of nucleosomes from transcribed genes in a transcription-dependent manner following yFACT depletion, which was accompanied by the appearance of short transcripts that originated from cryptic TSSs within the coding regions of yeast genes [66,[78][79][80][81][82][83][84][85]. FACT was also shown to be a critical factor in the repression of cryptic initiation of intragenic promoters genome-wide in plants [86].These data cumulatively suggest that in vivo, yFACT is clearly important for preserving chromatin structure at transcribed genes.…”
Section: Fact In Transcriptionmentioning
confidence: 99%
“…Mutations in SPT16 made the promoter of SER3 accessible for transcriptional factors and therefore derepressed the SER3 gene [78]. Multiple subsequent studies have reported loss of nucleosomes from transcribed genes in a transcription-dependent manner following yFACT depletion, which was accompanied by the appearance of short transcripts that originated from cryptic TSSs within the coding regions of yeast genes [66,[78][79][80][81][82][83][84][85]. FACT was also shown to be a critical factor in the repression of cryptic initiation of intragenic promoters genome-wide in plants [86].These data cumulatively suggest that in vivo, yFACT is clearly important for preserving chromatin structure at transcribed genes.…”
Section: Fact In Transcriptionmentioning
confidence: 99%
“…Thus, transcription of a non-coding RNA through the promoter of a nearby gene may lead to the inhibition of transcription of that gene. There are examples of this in yeast [8185], and it likely occurs in higher eukaryotes, which means that pervasive transcription not only generates useless transcripts and activates endogenous viruses, but also leads to the loss or alterations of expression of necessary transcripts encoding proteins. It is likely that genome-wide opening of chromatin promotes multiple instances of cryptic transcription initiation which will, in turn, disturb expression of nearby genes.…”
Section: Why Is Chromatin Destabilization Toxic?mentioning
confidence: 99%
“…Consistent with roles in both forming and bypassing nucleosomes, FACT participates in a range of processes including DNA transcription, replication, and repair 1315 . Notably, FACT is needed for efficient removal of nucleosomes during induction of transcription 16,17 , it facilitates nucleosome recovery during elongation and nucleosome repopulation during repression of transcription 1820 and it promotes transcription through chromatin by RNA polymerase II in vitro 21,22 , highlighting the importance of both its stabilization and destabilization activities.…”
Section: Introductionmentioning
confidence: 99%